Influences of Probe’s Morphology for Metal Ion Detection Based on Light-Addressable Potentiometric Sensors - Shao, Chen (Sensors (Basel), 2016)
The sensing mechanism of binding Hg(2+) into thymine-thymine (T-T) mismatched base pairs was introduced into a light-addressable potentiometric sensor (LAPS) with anti-Hg(2+) aptamer as the sensing units. Three kinds of T-rich single-strand DNA (ssDNA) chains with different spacer lengths, from 0 to 12 –CH(2) groups, were designed to investigate surface charge and morphological effects on the LAPS’ output. First, by comparing the responding of LAPS modified with three kinds of ssDNA, it was found that the best performance for Hg(2+) sensing was exhibited by the probe without –CH(2) groups. The detection limit of Hg(2+) ion was 1 ppt under the optimal condition. Second, the cooperative effects of surface charge and morphology on the output were observed by the controlled experiments. The two effects were the negative charge balanced by metal cations and the morphological changing caused by the formation of T-Hg(2+)-T structure. In conclusion, not only the influences of the aptamer probe’s morphology and surface charge was investigated on the platform of LAPS, but also sensing Hg(2+) ions was achieved for the first time by the presented aptamer LAPS.